2023
DOI: 10.1371/journal.pone.0285714
|View full text |Cite
|
Sign up to set email alerts
|

The military spouse experience of living alongside their serving/veteran partner with a mental health issue: A systematic review and narrative synthesis

Abstract: Introduction Military healthcare studies have reported a wide range of mental health issues amongst military personnel. Globally, mental health issues are one of the main causes of ill health. Military personnel have a greater prevalence of mental health issues than that of the general population. The impact of mental health issues can be wide and far reaching for family and carers. This systematic narrative review explores the military spouse experience of living alongside their serving or veteran partner wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Family functioning can also be negatively affected by the veteran’s separation from family for extended periods of time leading to a broader lack of connection ( 25 ). Furthermore, such a lack of connection may have negative effects on marital quality, relationship satisfaction, and the mental health of all military family members ( 26 ). Communication patterns, relationship quality, and parenting may also be impacted by the psychological distress of the veteran ( 12 , 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Family functioning can also be negatively affected by the veteran’s separation from family for extended periods of time leading to a broader lack of connection ( 25 ). Furthermore, such a lack of connection may have negative effects on marital quality, relationship satisfaction, and the mental health of all military family members ( 26 ). Communication patterns, relationship quality, and parenting may also be impacted by the psychological distress of the veteran ( 12 , 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…One systematic review focused on military personnel with mental disorders - regardless of deployment. The authors found negative influences on intimate relationships and psychological/psychosocial effects on the spouse ( 26 ).…”
Section: Introductionmentioning
confidence: 99%